Anemia falciforme: manifestações clínicas e diagnóstico laboratorial - Maldaner, Camila Betina (My University, 2023)
Introduction: Sickle cell anemia is a hereditary hematological disease with a hemoglobin disorder in the ß-globin gene. Characterized by the presence of drepanocytes whose predominant content is hemoglobin S in conditions of hypoxia Objective: to analyze what are the clinical aspects of Sickle Cell Anemia and what are the methods for making the diagnosis. Method: literature review, in which consultations were obtained in books, dissertations and scientific articles selected through a search in online databases, between the period 2013 and 2023. Results: The diagnosis of hemoglobinopathies is complex and involves an analysis that must be considered, in addition to clinical data and genetic inheritance, several factors such as the age of the individuals. Conclusion: the pathophysiological changes of sickle cell anemia can sometimes seriously interfere in the daily lives of individuals with it, understanding that early identification is essential, bringing an improvement in the quality of life of patients. [resumo fornecido pelo autor]
Introdução: a anemia falciforme é uma doença hematológica hereditária com o distúrbio da hemoglobina no gene da ß-globina. Caracterizada pela presença de drepanócitos cujo conteúdo predominante é a hemoglobina S em condições de hipóxia Objetivo: analisar quais são os aspectos clínicos da Anemia Falciforme e quais são os métodos para a realização do diagnóstico. Método: revisão de literatura, no qual obteve consultas em livros, dissertações e artigos científicos selecionados através de busca nas bases de dados online, entre o período de 2013 a 2023. Resultados: O diagnóstico das hemoglobinopatias é complexo e envolve uma análise que deve considerar dados clínicos, herança genética, idade, sexo, entre outros fatores. Conclusão: as alterações fisiopatológicas da anemia falciforme, podem por vezes intervir seriamente no cotidiano de indivíduos portadores, compreendendo que a identificação precoce é essencial, trazendo uma melhora na qualidade de vida dos pacientes. [resumo fornecido pelo autor]
Keywords: Anemia falciforme; Diagnóstico de laboratório; Hemoglobina; Hemoglobinopatia